Esotericism in East Asia (Bloomsbury Publishing (UK), 2026)
This pioneering open access book offers a new take on esotericism by centering the often-overlooked contributions of East Asian thinkers to the development of this field of knowledge. The intellectual history of esotericism has long revolved around Western ideas about the East. This book tells a more complex and accurate story that traces global exchanges of ideas across East and West. Esotericism in East Asia critically examines how and why the language of ‘esotericism’ has become so ubiquitous in scholarship on Asian religious ideas and practices. It highlights the role of interactions between European and Asian scholars since the 16th century to show that Asian thinkers and their local contexts have crucially shaped our understanding of esotericism. With contributions focusing on a range of contexts in Japan and China, from Buddhism and Shinto to the Theosophical movement and occultism, this volume provides rich insights into how Asians have engaged with and influenced the study of esotericism across the globe. By introducing a new framework for studying esotericism in Asia from a perspective of global cultural exchange, this volume provides an important corrective to the Eurocentric approaches to studying esotericism that have dominated Western scholarship. As an invaluable reference for scholars working at the intersection of East Asian studies and esotericism, it lays the groundwork for more nuanced scholarship in the field. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the University of Göttingen .